2020
DOI: 10.1039/d0ra05986b
|View full text |Cite
|
Sign up to set email alerts
|

Development of starch based intelligent films by incorporating anthocyanins of butterfly pea flower and TiO2 and their applicability as freshness sensors for prawns during storage

Abstract: Anthocyanin extracted from butterfly pea flower incorporated starch/TiO2 films are excellent pH indicator for monitoring the freshness of food sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…Another study used anthocyanin extract from blue pea flowers in a freshness monitoring packaging for prawns made with starch and TiO 2 . The colour of the colour indicator changed from pink to green when prawns were stored at 4 • C for 6 days (Mary et al, 2020). Similarly, Wu et al (2021) developed an intelligent packaging film using gellan gum adding blue pea flower anthocyanin extract to monitor the freshness of shrimp.…”
Section: Applications Of Anthocyanins From Blue Pea Flowermentioning
confidence: 99%
“…Another study used anthocyanin extract from blue pea flowers in a freshness monitoring packaging for prawns made with starch and TiO 2 . The colour of the colour indicator changed from pink to green when prawns were stored at 4 • C for 6 days (Mary et al, 2020). Similarly, Wu et al (2021) developed an intelligent packaging film using gellan gum adding blue pea flower anthocyanin extract to monitor the freshness of shrimp.…”
Section: Applications Of Anthocyanins From Blue Pea Flowermentioning
confidence: 99%
“…Several studies have shown eco-efficient alternatives for developing antibacterial nanocomposites based on TiO 2 NPs. The extraction of plant compounds has been a widely used alternative in the preparation of sustainable food packaging films (Chi et al, 2019;Liu et al, 2021c;Mary et al, 2020). Recently, Lan et al (2021) introduced TiO 2 NPs in systems based on CS and red apple pomace extract (APE) for the production of antibacterial films against E. coli and S. aureus (Figure 3B).…”
Section: Titanium Dioxide (Tio 2 ) Nanoparticlesmentioning
confidence: 99%
“…Several studies have shown eco‐efficient alternatives for developing antibacterial nanocomposites based on TiO 2 NPs. The extraction of plant compounds has been a widely used alternative in the preparation of sustainable food packaging films (Chi et al., 2019; Liu et al., 2021c; Mary et al., 2020). Recently, Lan et al.…”
Section: Overview Of Inorganic Nanoparticles Applied In Nanocompositesmentioning
confidence: 99%
“…1 The high activity of microorganisms in meat spoilage causes high production of volatile base compounds such as dimethylamine, trimethylamine and ammonia. 2 The COVID-19 pandemic has forced most consumers to shop for food products quickly, spend less time in public places and pay more attention to food safety and freshness. The development of intelligent packaging provides time efficiency and food security for consumers by providing real-time information on the quality of food products.…”
Section: Introductionmentioning
confidence: 99%